2006
DOI: 10.1111/j.1365-2958.2006.05402.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulated intramembrane proteolysis of FtsL protein and the control of cell division in Bacillus subtilis

Abstract: SummaryThe small bitopic division protein FtsL is an essential part of the division machinery (divisome) in most eubacteria. In Bacillus subtilis FtsL is a highly unstable protein and the turnover has been implicated in regulation of division in response to DNA damage. N-terminal deletions and a domain swap experiment identified the short cytoplasmic domain of FtsL as being required for instability. We then identified a zinc metalloprotease, YluC, required for turnover, and likely sequence motifs involved in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
83
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(91 citation statements)
references
References 50 publications
(84 reference statements)
6
83
0
2
Order By: Relevance
“…Both enzymes have been implicated in the cellular response to the stresses caused by high-level production of secretory proteins or heat, but whether this involves a sheddase activity of HtrA or HtrB is not known (30,62,187). Interestingly, the cellular levels of HtrA and HtrB seem to be controlled by RasP, the RseP homologue of B. subtilis, suggesting that they are subject to intramembrane cleavage (19,199). This would explain why fragments of HtrA and HtrB are detectable in the growth medium of B. subtilis.…”
Section: Degsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both enzymes have been implicated in the cellular response to the stresses caused by high-level production of secretory proteins or heat, but whether this involves a sheddase activity of HtrA or HtrB is not known (30,62,187). Interestingly, the cellular levels of HtrA and HtrB seem to be controlled by RasP, the RseP homologue of B. subtilis, suggesting that they are subject to intramembrane cleavage (19,199). This would explain why fragments of HtrA and HtrB are detectable in the growth medium of B. subtilis.…”
Section: Degsmentioning
confidence: 99%
“…In the enteric pathogen Vibrio cholerae, the causative agent of cholera, DegS is implicated in sigma E-mediated resistance to membrane-acting, host gut-derived antimicrobial peptides (103). In B. subtilis, the DegS homologue proteases HtrA and HtrB are both membrane bound by an N-terminal membrane anchor like E. coli DegS (7,19,62,198,199). Both enzymes have been implicated in the cellular response to the stresses caused by high-level production of secretory proteins or heat, but whether this involves a sheddase activity of HtrA or HtrB is not known (30,62,187).…”
Section: Degsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are also involved in the endoplasmic reticulum stress responses (6 -8). Recent studies revealed that the prokaryotic S2P homologs function in membranebased events such as stress response (9), sporulation (10), cell division (11), and cell differentiation (12). In Escherichia coli, the S2P homolog RseP is an essential player in the transmembrane signaling involved in the E pathway of extracytoplasmic stress responses (13)(14)(15).…”
Section: I-clipsmentioning
confidence: 99%
“…Recently, it has been demonstrated that FtsL, a transmembrane protein of the B. subtilis cell division machinery, is attacked by RasP (Bramkamp et al, 2006). Therefore, in analogy to the GFP-RsiW reporter, a GFP-FtsL fusion was constructed and expressed in different genetic backgrounds.…”
Section: Mutations In B Subtilis Ecsab Prevent Induction Of S W -Conmentioning
confidence: 99%